Frontal deficits and atrophy in a patient with familial encephalopathy with neuroserpin inclusion bodies detected by single-case voxel-based morphometry: a case report - Hideo Handa; Atsuhiko Sugiyama; Tadashi Kaname; Yoko Shigemoto; Noriko Sato; Shigeki Hirano; Yuki Nakagawa; Akiyuki Uzawa; Akiyo Aotsuka; Satoshi Kuwabara (BMC Neurology, 2024)
Abstract Background Familial encephalopathy with neuroserpin inclusion bodies (FENIB) is a rare genetic disorder characterized by progressive cognitive decline and myoclonic epilepsy, caused by pathogenic variants of SERPINI1. We reported a case of genetically confirmed FENIB with de novo H338R mutation in the SERPINI1, in which frontal deficits including inattention and disinhibition, and relevant atrophy in the vmPFC on brain MRI were observed in the early stage of the disease. Case presentation A 23-year-old Japanese man presented with progressive inattention and disinhibition over 4 years followed by myoclonic epilepsy. The whole-genome sequencing and filtering analysis showed de novo heterozygous H338R mutation in the SERPINI1, confirming the diagnosis of FENIB. Single-case voxel-based morphometry using brain magnetic resonance imaging obtained at the initial visit revealed focal gray matter volume loss in the ventromedial prefrontal cortices, which is presumed to be associated with inattention and disinhibition. Conclusion Frontal deficits including inattention and disinhibition can be the presenting symptoms of patients with FENIB. Single-case voxel-based morphometry may be useful for detecting regional atrophy of the frontal lobe in FENIB. Detecting these abnormalities in the early stage of disease may be key findings for differentiating FENIB from other causes of progressive myoclonic epilepsy.